Fin tech 5.0: The journey from cryptocurrency to neobanking - Chakraborti, Jayanta; Aggarwal, Shalini; Kumar, Pardeep (London Routeldge, 2025)
This book offers comprehensive knowledge on, and the applications of, the rapidly evolving financial technology landscape. Authored by seasoned experts, it serves as a vital resource for both students and practitioners in the fintech sector.